2009
DOI: 10.1021/es9007917
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation Induced by Expandable Clay Minerals

Abstract: Small-sized environmental particles such as 2:1 phyllosilicates induce oxidative stress, a primary indicator of cell damage and toxicity. Herein, potential hazards of clay particle uptake are addressed. This paper reports that the content and distribution of structural Fe influence the ability of expandable clay minerals to induce lipid peroxidation (LP), a major indicator of oxidative stress, in biological matrices. Three smectite clays, hectorite (SHCa-1) and two nontronites (NAu-1) and (NAu-2) containing va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Table 3 (top, 5th and 6th columns) show a higher extent of As(III) conversion in the presence of NAu-2 over NAu-1. These results agree well with reports on the higher reactivity of NAu-2 over NAu-1 as evidenced by their relative ability to induce lipid peroxidation, a major indicator of oxidative stress [34], for example. Existing structural differences between NAu-1 and NAu-2 are associated with the distribution of structural iron over the total structural iron content alone (35.21 and 37.85% Fe 2 O 3 , respectively; [3]).…”
Section: Nontronitesupporting
confidence: 92%
“…Table 3 (top, 5th and 6th columns) show a higher extent of As(III) conversion in the presence of NAu-2 over NAu-1. These results agree well with reports on the higher reactivity of NAu-2 over NAu-1 as evidenced by their relative ability to induce lipid peroxidation, a major indicator of oxidative stress [34], for example. Existing structural differences between NAu-1 and NAu-2 are associated with the distribution of structural iron over the total structural iron content alone (35.21 and 37.85% Fe 2 O 3 , respectively; [3]).…”
Section: Nontronitesupporting
confidence: 92%
“…Regarding oxidative stress biomarkers, Kibanova et al (2009) reported that nontronites induced higher LPO than hectorite in brain supernatant solutions exposed to up to 1000 ppm. Maisanaba et al (2014e), however, did not find any alteration in the LPO, SOD, GPx and GST activities in the liver and kidney of rats exposed for 90 days to a 40 mg/kg bw/d Mt-modified clay (Clay1), although the CAT activity, gene expression and protein abundance were increased in the kidney.…”
Section: In Vivo Toxicological Assaysmentioning
confidence: 99%
“…Several researchers have already evaluated the in vitro toxicological profiles of different clays and derived nanocomposites, concluding that the toxicity shown depends on various parameters, the most important of which were the modifiers used, the experimental model selected, the concentration range and the exposure times (Section 2). Regarding the in vivo assessments, although it has been recognized that the interaction of clays with organs may provoke health-deleterious consequences, to date, there is little mechanistic understanding of the physiological effects due to exposure to clays (Kibanova et al, 2009). Some studies performed in vivo can be found in the literature, and different results have been published (Section 3).…”
Section: Introductionmentioning
confidence: 99%
“…Lipids recovered from supernatants of rat brain homogenate were used. All incubations lasted 4 h [26,27]. The contents of TBARS in sepiolite or palygorskite dispersions were compared against negative controls ( Fig.…”
Section: Lipid Peroxidationmentioning
confidence: 99%